Differential effects of extracellular vesicles from aging and young mesenchymal stem cells in acute lung injury - Huang, Ruoqiong (Aging (Albany NY), 2019)
Old age is a known risk factor for mortality in acute respiratory distress syndrome (ARDS)/acute lung injury. Mesenchymal stem cells (MSCs) possess potent immunomodulatory properties, while aging MSCs have reduced capacity. Recent studies have demonstrated that MSC-derived extracellular vesicles (MSC-EVs) are able to mimic MSCs in alleviating acute lung injury. The goals of this study were to determine whether EVs from young and aging MSCs had differential effects on lipopolysaccharide (LPS)-induced lung injury in young mice and unravel the underlying mechanisms. Our results showed that both aging and young MSC-EVs had similar physical and phenotypical properties. As their parental cells, young MSC-EVs alleviated LPS-induced acute lung injury, while aging MSC-EVs did not exhibit the protective effects. In contrast to young MSC-EVs, aging MSC-EVs failed to alter macrophage phenotypes and reduce macrophage recruitment. In addition, the internalization of aging MSC-EVs by macrophages was significantly lower compared with that of young MSC-EVs. Furthermore, aging and young MSC-EVs differed in levels of several miRNAs relating macrophage polarization. In conclusion, aging and young MSC-EVs have differential effects in alleviating acute lung injury and macrophage polarization, which may be associated with internalization of EVs and their miRNA content.